Chromosome identification and reconstruction of evolutionary rearrangements in Brachypodium distachyon, B. stacei and B. hybridum. (8th June 2018) - Lusinska, Joanna; Majka, Joanna; Betekhtin, Alexander; Susek, Karolina; Wolny, Elzbieta; Hasterok, Robert
Abstract: Background and Aims: The Brachypodium genus represents a useful model system to study grass genome organization. Palaeogenomic analyses (e.g. Murat F, Armero A, Pont C, Klopp C, Salse J. 2017. Reconstructing the genome of the most recent common ancestor of flowering plants. Nature Genetics 49 : 490–496) have identified polyploidization and dysploidy as the prime mechanisms driving the diversity of plant karyotypes and nested chromosome fusions (NCFs) crucial for shaping grass chromosomes. This study compares the karyotype structure and evolution in B. distachyon (genome Bd), B. stacei (genome Bs) and in their putative allotetraploid B. hybridum (genomes BdBs). Methods: Brachypodium chromosomes were measured and identified using multicolour fluorescence in situ hybridization (mcFISH). For higher resolution, comparative chromosome barcoding was developed using sets of low-repeat, physically mapped B. distachyon -derived bacterial artificial chromosome (BAC) clones. Key Results: All species had rather small chromosomes, and essentially all in the Bs genome were morphometrically indistinguishable. Seven BACs combined with two rDNA-based probes provided unambiguous and reproducible chromosome discrimination. Comparative chromosome barcoding revealed NCFs that contributed to the reduction in the x = 12 chromosome number that has been suggested for the intermediate ancestral grass karyotype. Chromosome Bd3 derives from two NCFs of three ancestral chromosomes (Os2, Os8, Os10). Chromosome Bs6 shows an ancient Os8/Os10 NCF, whilst Bs4 represents Os2 only. Chromosome Bd4 originated from a descending dysploidy that involves two NCFs of Os12, Os9 and Os11. The specific distribution of BACs along Bs9 and Bs5, in both B. stacei and B. hybridum, suggests a Bs genome-specific Robertsonian rearrangement. Conclusions: mcFISH-based karyotyping identifies all chromosomes in Brachypodium annuals. Comparative chromosome barcoding reveals rearrangements responsible for the diverse organization of Bd and Bs genomes and provides new data regarding karyotype evolution since the split of the two diploids. The fact that no chromosome rearrangements were observed in B. hybridum compared with the karyotypes of its phylogenetic ancestors suggests prolonged genome stasis after the formation of the allotetraploid.